New species of Antocha Osten Sacken, 1860 crane flies (Diptera: Limoniidae) for South Korea - Podenas, Sigitas; Byun, Hye-Woo (Zootaxa, 2014)
New species Antocha (Antocha) koreana from South Korea is described and illustrations of the distinguishing morphological features, including wing venation, male and female genitalia and male antenna, are provided with a discussion on distinguishing newly described species from other similar species. Habitat information for new species is presented. Antocha (Antocha) subconfluenta Alexander, 1930 is new record for Korean fauna and first record from outside Japan.